Mucosal Healing in Inflammatory Bowel Diseases: Is There a Place for Nutritional Supplementation?. Issue 1 (January 2015) - Lan, Annaïg; Blachier, François; Benamouzig, Robert; Beaumont, Martin; Barrat, Christophe; Coelho, Desire; Lancha, Antonio; Kong, Xiangfeng; Yin, Yulong; Marie, Jean-Claude; Tomé, Daniel
Abstract : Abstract: Advanced mucosal healing (MH) after intestinal mucosal inflammation coincides with sustained clinical remission and reduced rates of hospitalization and surgical resection, explaining why MH is increasingly considered as a full therapeutic goal and as an endpoint for clinical trials. Intestinal MH is a complex phenomenon viewed as a succession of steps necessary to restore tissue structure and function. These steps include epithelial cell migration and proliferation, cell differentiation, restoration of epithelial barrier functions, and modulation of cell apoptosis. Few clinical studies have evaluated the needs for specific macronutrients and micronutrients and their effects on intestinal MH, most data having been obtained from animal and cell studies. These data suggest that supplementation with specific amino acids including arginine, glutamine, glutamate, threonine, methionine, serine, proline, and the amino acid-derived compounds, polyamines can favorably influence MH. Short-chain fatty acids, which are produced by the microbiota from undigested polysaccharides and protein-derived amino acids, also exert beneficial effects on the process of intestinal MH in experimental models. Regarding supplementation with lipids, although the effects of ω-3 and ω-6 fatty acids remain controversial, endogenous prostaglandin synthesis seems to be necessary for MH. Finally, among micronutrients, several vitamin and mineral deficiencies with different frequencies have been observed in patients with inflammatory bowel diseases and supplementation with some of them (vitamin A, vitamin D3, vitamin C, and zinc) are presumed to favor MH. Future work, including clinical studies, should evaluate the efficiency of supplementation with combination of dietary compounds as adjuvant nutritional intervention for MH of the inflamed intestinal mucosa. Abstract : Article first published online 9 September 2014.